2023
DOI: 10.3390/educsci13070730
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Students’ Interaction in Higher Education: A Reciprocal Interview Activity Carried out during the First Class Session in Management Subjects

Abstract: This study analyzes students’ thoughts and reflections on an activity carried out during the first day of class of management subjects which are part of technological programs. The purpose of the activity was to promote student interaction during the first session of class of these subjects, with the aim to positively influence the class climate and the students’ wellbeing. A reciprocal interview activity between the students and the team of instructors was conducted in the first session of the subjects, inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Another defining feature of integrated health and well-being solutions should be pro-active monitoring of students' needs in the mental, physical, university learning, and economic well-being domains. Through such monitoring, universities should offer greater engagement between academics, administrators, alumni, and students, using academic and non-academic agendas to provide long-term help to each other [15,36,37]. For instance, at the university under study, the mental/psychological well-being of students is identified as an area needing improvement, being the domain that received the lowest score among all the well-being domains.…”
Section: Discussionmentioning
confidence: 99%
“…Another defining feature of integrated health and well-being solutions should be pro-active monitoring of students' needs in the mental, physical, university learning, and economic well-being domains. Through such monitoring, universities should offer greater engagement between academics, administrators, alumni, and students, using academic and non-academic agendas to provide long-term help to each other [15,36,37]. For instance, at the university under study, the mental/psychological well-being of students is identified as an area needing improvement, being the domain that received the lowest score among all the well-being domains.…”
Section: Discussionmentioning
confidence: 99%